Effect of Every-other-day Fasting on Level of Serum TNF-α in Rats after Acute Spinal Cord Injury - Jiancheng LIU; Wenchun WANG; Shaojie LUO; Yanbo LI; Yunhui ZHAO; Rizhao PANG; Chao DONG; Shanshan ZHANG; Anren ZHANG (康复学报)
Objective:To observe the effect of every-other-day fasting (EODF) on serum tumor necrosis factor-α (TNF-α) level in rats after acute spinal cord injury.Methods:A total of 48 female adult Wistar rats were randomly divided into EODF group (group A), normal diet control group (group B) and sham-operated group (group C). Thoracic spinal cord injury models were established in rats of group A and group B by modified Allen contusion method, and laminectomy was performed in rats of group C. Then group A received EODF, group B and group C were given a normal diet immediately after operation.BBB scores were calculated in each group at 6 hours, 1st day, 3rd day and 7th day after operation to observe the motor function changes, then the rats were killed and their serum was taken. The level of TNF-α in serum was detected by ELISA.Results:Severe hindlimb motor dysfunction of rats was found in group A and group B after operation, and there were significant differences in BBB scores between the two groups at 3rd day and 7th day after operation (P<0.05). The level of serum TNF-α was increased in group A and group B after operation, and there were significant differences in the index between the two groups at 1st day, 3rd day and 7th day after operation (P<0.05).Conclusion:EODF can improve the hind limb motor function of rats after acute spinal cord injury. The mechanism may be related with suppressing expression of inflammatory cytokines TNF-α, inhibiting inflammatory response and reducing secondary injury.